Using intelligent text recognition to create audiobooks for blind people - Silchenko, V.; Chebotarova, I. (My University, 2024)
The modern information environment is extremely difficult for blind people. It is now extremely important to implement projects aimed at inclusion, so that everyone has the opportunity to spend their leisure time or study in a way that is convenient for them.
Keywords: text; recognition